Pengaruh Program Keselamatan dan Kesehatan Kerja (K3) terhadap Produktivitas Kerja Karyawan dalam Issue Covid-19 - Ari Dwi Purba; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
ABSTRACK. This The world is currently faced with the emergence of the Covid-19 virus pandemic. The virus, which initially developed in the Chinese city of Wuhan in December 2019, has now spread widely throughout the world, including Indonesia. The impact of the Covid-19 pandemic has changed business and work patterns. Likewise with the K3 Program and Employee Work Productivity at PT. Tekniko Indonesia also underwent changes. The purpose of this study is to find out 1) To find out the K3 Program in the Covid-19 Issue at PT. Tekniko Indonesia. 2) To find out how the work productivity of employees at PT. Tekniko Indonesia. 3) To analyze how the OSH Program affects the Work Productivity of the Covid-19 Issue. This research was conducted at PT. Tekniko Indonesia which is engaged in Steel Construction and Fabrication was established in 1997. The research method used in the form of descriptive analysis and verification of data processing using SPSS 25.0 for windows program. The sampling method used simple random sampling technique. With the number of respondents as many as 51 employees of the company PT. Tekniko Indonesia. The independent variable studied in the study was in the form of the K3 Program while the dependent variable was in the form of Employee Work Productivity. Data collection is done by using a questionnaire. The results of this study conclude that: 1) The K3 Program Variables are included in the very high category. 2) Employee Productivity Variables are included in the very high category. 3) The influence of the K3 Program variable is 83.3%. 4) The K3 Program variable has a significant influence on Employee Work Productivity in the Covid-19 Issue at PT. Tekniko Indonesia. ABSTRAK. Saat ini dunia tengah dihadapkan dengan munculnya pandemi virus Covid-19. Virus yang pada awalnya berkembang di Kota Wuhan China pada Desember 2019 lalu, kini telah menyebar luas hampir ke seluruh dunia termasuk Indonesia. Dampak pandemi Covid-19 telah mengubah pola bisnis dan kerja. Begitu pula dengan Program K3 dan Produktivitas Kerja Karyawan di PT. Tekniko Indonesia juga mengalami perubahan. Tujuan dari penelitian ini untuk mengetahui 1) Untuk mengetahui Program K3 dalam Issue Covid-19 pada PT. Tekniko Indonesia. 2) Untuk mengetahui bagaimana Produktivitas Kerja karyawan pada PT. Tekniko Indonesia. 3) Untuk menganalisis bagaimana pengaruh Program K3 terhadap Produktivitas Kerja karyawan Issue Covid-19. Penelitian ini dilaksanakan pada PT. Tekniko Indonesia yang bergerak dalam bidang Konstruksi dan Fabrikasi baja berdiri pada tahun 1997. Adapun metode penelitian yang digunakan berupa analisis deskriptif dan verifikatif yang pengolahan datanya menggunakan bantuan program SPSS 25.0 for windows. Metode penarikan sampel menggunakan teknik simple random sampling. Dengan jumlah responden sebanyak 51 orang karyawan perusahaan PT. Tekniko Indonesia. Variabel bebas yang dikaji dalam penelitian berupa Program K3 sedangkan untuk variabel terikat berupa Produktivitas Kerja Karyawan. Pengumpulan data dilakukan dengan menggunakan kuisioner. Hasil dari penelitian ini menyimpulkan bahwa: 1) Variabel Program K3 termasuk dalam kategori sangat tinggi. 2) Variabel Produktivitas Kerja Karyawan termasuk dalam kategori sangat tinggi. 3) Pengaruh variabel Manajmen K3 sebesar 83,3%. 4) Variabel Program K3 memiliki pengaruh signifikan terhadap Produktivitas Kerja Karyawan dalam Issue Covid-19 di PT. Tekniko Indonesia.